HUBUNGAN ANTARA SPIRITUALITAS DENGAN SUBJECTIVE WELL-BEING PADA PEREMPUAN KAMPUNG LAMPION MALANG PADA MASA PANDEMI COVID-19 - Nuryanti, Sofia; Mumtazah, Salsabila; Sari, Galuh Pavita (JURNAL TALENTA PSIKOLOGI, 2021)
The COVID-19 pandemic can cause stress to individuals who feel anxious and afraid of uncertainty in all uncertain situations. This has an impact on the individual's state of well-being. This study aims to determine the relationship between spirituality and subjective well-being in the women of Kampung Lampion Malang during the COVID-19 pandemic. A quantitative approach is used in this study to determine the relationship between spirituality and subjective well being using a simple linear correlation. Using a purposive sampling technique, as many as 103 women living in Kampung Lampion Malang, aged between 18 - 60 years and willing to be respondents. The measuring instrument used to measure the spirituality variable is the Daily Spiritual Experience Scale (DSES) developed by Underwood and Teresi (2002). ) with (Î±=0.927). Researchers used measuring instruments SWLS (Î± = 0.826) and SPANE (Î± = 0.682) from Diener (1984) which were used to measure subjective well being. The results of the simple correlation Pearson's Correlation obtained a significance value of 0.001 (p<0.05) with a correlation value of 0.452 which it can be concluded that there is a relationship between spirituality and subjective well-being in women in Kampung Lampion, Malang City